Neutrophil to Lymphocyte Ratio in Patients with Major Depressive Disorder (Journal of Armed Forces Medical College, Bangladesh, 2024)
Introduction: Depression is common mood disorder that is linked to systemic inflammation. The neutrophil-lymphocyte ratio (NLR) is a non-specific inflammatory marker that is inexpensive and easy to measure. Low-grade inflammation occurs in a subgroup of patients with Major Depressive disorder (MDD).Objective: To examine the role of inflammation in the etiology of depression based on the NLR in MDD patients who are undergoing no pharmacological therapy.Methods: This observational study was carried out in the Department of Psychiatry of Jahurul Islam Medical College Hospital (JIMCH), Bajitpur, Kishoregonj between December 2013 and May 2014. Subjects between the ages of 18 and 65 were included in the study that involved 61 subjects with diagnosed MDD, who received no pharmacological therapy of depression within the past 01 month were included in the study, while the control group included 67 healthy subjects with having no psychiatric disease. A sociodemographic information form and a Beck Depression Scale were administered, and the blood was taken for biochemical analysis and complete blood parameters were evaluated in the hematology laboratory of JIMCH. All data were expressed as mean±SD. For statistical analysis, Chi-square test (χ2) was used to compare categorical variables, frequencies, and ratios. An independent sample ‘t’ test was used to compare normally distributed variables between two groups.Results: In the present study, we found Significance difference in the NLR, neutrophil count, lymphocyte percentage and leukocyte values of the patient group when compared with control group (P